2019
DOI: 10.14336/ad.2018.1024
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Activation is Associated with Neuroprotection in Diabetes-associated Cognitive Decline

Abstract: Autophagy is a lysosome-dependent cellular catabolic mechanism that mediates the turnover of dysfunctional organelles and aggregated proteins. It has a neuroprotective role on neurodegenerative diseases. Here, we hypothesized that autophagy may also have a neuroprotective role in diabetes-associated cognitive decline (DACD). In current study, we found that db/db mice display cognitive decline with inferior learning and memory function. The accumulation of β-amyloid1-42 (Aβ1-42), which is a characteristic of Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 52 publications
(55 reference statements)
1
15
0
Order By: Relevance
“…Furthermore, Aβ 1-42 was largely deposited in the hippocampus of db/db mice, and synaptic dysfunction in the hippocampus was presented in db/db mice. These findings are consistent with our and others' previous studies [1,31]. With the increasing epidemic of FGF1 has dual function of normalizing hyperglycemia [23] and neuroprotection [32].…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, Aβ 1-42 was largely deposited in the hippocampus of db/db mice, and synaptic dysfunction in the hippocampus was presented in db/db mice. These findings are consistent with our and others' previous studies [1,31]. With the increasing epidemic of FGF1 has dual function of normalizing hyperglycemia [23] and neuroprotection [32].…”
Section: Discussionsupporting
confidence: 93%
“…Studies have demonstrated that autophagy plays a protective role in diabetes and IVDD 39 ; also, autophagy has been shown to combat against senescence 25 . Based on in vitro investigation, we found that HuR regulates senescence through autophagy.…”
Section: Discussionmentioning
confidence: 70%
“…Increasing evidence indicated that DM is related to cognitive impairment, and the level of hyperglycemia and duration of DM have been shown to be linked with cognitive decline [23]. Cerebrovascular dysfunction is associated with cognitive impairment in patients with vascular dementia [24].…”
Section: Diabetes Enhanced Cerebral Lesion Deteriorates Cognitive Impmentioning
confidence: 99%